THE DEVELOPMENT OF THE NATIONAL LEGAL FRAMEWORK ON THE BASES AND FOUNDATIONS FOR BUILDINGS AND STRUCTURES DESIGN - Slyusarenko, Yu. S.; Titarenko, V. A.; Melashenko, Yu. B.; Shuminskiy, V. D.; Zotsenko, М. L.; Vynnykov, Yu. L. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The main document of the regulatory framework for the bases and foundations of buildings and structures design is DBN V.2.1-10-2009 (with Amendments No. 1 and No. 2). For the replacement of existing DBN it is proposed to develop a system of regulatory documents that will include DBN V.2.1-10:201Х «Bases and foundations of buildings and structures. Main provisions» and standards for its development. The project provides the principles (general provisions) and requirements regarding the design, construction and reconstruction of bases and foundations for the buildings and structures of all types and classes of consequences (responsibility). The attention is focused on the peculiarities of foundations calculations according to design features and interactions with the base and various depth foundation design.
Keywords: bases; foundations; buildings; structures; class of consequences (responsibility); design; construction